The use of adrenaline in cardiac arrest - impact on survival to discharge from the hospital - Zimnicki, Patryk; Lato, Marta; Iberszer, Konrad; Litwiniuk, Maria; Zaniuk, Marcin; Hurkała, Kamil; Antonik, Dominika; Denys, Barbara; Góra, Karolina; Zdziennicki, Wojciech (Journal of Education, Health and Sport, 2023)
Introduction and objective: Epinephrine is the most important and primary drug that resuscitation team use to reverse cardiac arrest. The provision of epinephrine is currently suggested by both the American Heart Association and the European Resuscitation Council. It is vital to improving the return of spontaneous circulation (ROSC), however the evidence for the use of adrenaline in resuscitation is inconclusive. Materials and methods: The literature was reviewed in the Pubmed database, in the Via Medica Journals database, and in the guidelines of the Polish Society of Anesthesiology, European Resuscitation Council and the American Heart Association with the use of keywords. State of knowledge: There is a clear evidence of an association between epinephrine and increased return of spontaneous circulation (ROSC). Its action is based on stimulation of alpha- and beta-adrenergic receptors. Epinephrine have a role in resuscitation, during CPR it increases the probability of restoring cardiac activity with pulses, which is intermediate step toward long-term survival. However, there are conflicting results regarding long-term survival and functional recovery, particularly neurological outcome. Conclusions: Research shows that epinephrine administration in patients with cardiac arrest increases the chance of restoring spontaneous circulation and patient survival to hospital admission and discharge. However, there are arguments questioning the validity of using epinephrine in resuscitation. Publications show that the compound contributes to post-resuscitation syndrome, which reduces a patient's chance of long-term survival. There are a number of conflicting studies that vary widely in the results presented. The current evidence is insufficient to either confirm or exclude the efficacy of epinephrine, which is why it is still recommended in the latest resuscitation guidelines by the European Resuscitation Council (ERC 2021) and the American Heart Association (AHA 2020).